Amino acid sequence of a myotoxic Lys49-phospholipase A2 homologue from the venom of Cerrophidion (Bothrops) godmani - de Sousa, Marcelo Valle (1998)
The complete amino acid sequence of myotoxin II (godMT-II), a myotoxic phospholipase A2 (PLA2) homologue from the venom of the Central American crotaline snake Cerrophidion (Bothrops) godmani, was determined by direct protein sequencing methods. GodMT-II is a class II PLA2 showing a Lys instead of Asp at position 49. An additional substitution in the calcium binding loop region (Asn instead of Tyr at position 28) suggests the lack of enzymatic activity observed in this toxin is due to loss of its ability to bind the co-factor Ca2+, since the residues involved in forming the catalytic network of PLA2s (His-48, Tyr-52 and Asp-99) are conserved in godMT-II. This myotoxin shows highest sequence homology with other Lys-49 PLA2 s from Bothrops, Agkistrodon and Trimeresurus species, suggesting that they constitute a conserved family of proteins, yet in contrast presents lower homology with Bothrops asper myotoxin III, a catalytically-active PLA2. The C-terminal region of godMT-II, which is rich in cationic and hydrophobic residues, shares high sequence homology to the corresponding region in the myotoxin II from B. asper, which has been proposed to play an important role in the Ca(2+)-independent membrane damaging activity.